CORE ETHICAL VALUES PENDIDIKAN KARAKTER BERBASIS NILAI-NILAI ISLAM - Ahmad Husni Hamim; Ani Rindiani; Aan Hasanah; Bambang Samsul Arifin (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2021)
This paper aims to reveal the values contained in the teachings of Islam that are character-laden. Islam is a religion rich in value. Islam is also used as a reference base in character education. So it can be said that when Muslims obey and obey the teachings then the Muslims are people of character, Muslim people who have character is a religiously obedient society that makes the world as a tool to collect supplies of the hereafter. Character education in general has a big goal that is to achieve akhlaqul karimah sourced from the Qur'an and Hadith. In character education based on the Qur'an and Hadith, educational materials can be broadly grouped in three dimensions of akhlah value, namely morality towards Allah Almighty. Some of the main characters that underlie other good characters contained in the Qur'an are: a) steadfast and unyielding, including patience, both passive and actively patient, b) consistent (istiqomah) whose consequences do not follow the passions, both that appear in him, as well as the bad desires of people, c) Integrity built from self-discipline, discipline to be honest , fair as it should be in every situation, d) professionalism that fosters quality mentality, altruistic mentality, learner mentality, and ethical menta